The crayons' Christmas - Daywalt, Drew; Jeffers, Oliver (New York : Penguin Workshop, 2019)
Duncan and his box of crayons celebrate the holidays by decorating the house, baking Christmas cookies, and sending and receiving letters from family.
Keywords: Crayons -- Fiction; Christmas -- Fiction; Letters -- Fiction